Poland as a(n) (un)attractive destination for Belarusian labour migrants: CARIM-East research report - Zuzanna Brunarska; Magdalena Lesińska (University of Warsaw, Centre of Migration Research (CMR), 2014)
Poland, due to its geographical and cultural proximity as well as stable economic growth in recent years, may be a natural destination country for labour migrants from Belarus. The statistics related to their residence and employment show that the numbers of Belarusians working in Poland are smaller than it could be expected, in particular, relatively smaller comparing to Ukrainians. The text analyzes the causes of the limited attractiveness of Poland as a destination country for labour migrants from Belarus and points to the external and internal determinants of migration processes of Belarusian population. The paper is based on variety of secondary sources and qualitative research - in-depth interviews with local experts conducted in Minsk, Grodno and Warsaw. The text consists of four parts. The first one is an overview of statistical data on migration of Belarusians. The next two sections focus on the main determinants of migration outflows of Belarusian population: external (including political and international situation of Belarus), and internal ones (economic and social determinants, labour market and social networks), which heavily influence individuals' decision on whether and where to migrate. The last section is devoted to Poland and its (un)attractiveness for labour migrants from Belarus, including the discussion of its strengths and weaknesses as a destination country.
Keywords: 330; labour migration; Belarus; Poland; determinants of migration processes